Pengembangan Handout Fisika Berbasis CORE (Connecting, Organizing, Reflecting and Extending) untuk Meningkatkan Higher Order Thinking Skills pada Peserta Didik SMA - Nurul Fatikhakh; Arif Maftukhin; Siska Desy Fatmaryanti (Universitas Muhammadiyah Purworejo, 2018)
Abstract – This study aims to: (1) Determine the feasibility of developing a CORE-based Physics handout. (2) Determine students' responses to the use of CORE-based Physics handouts. (3) Knowing the increase in students' HOTS after the use of a CORE-based Physics handout in the learning process. The type of research carried out is research and development, using the ADDIE development model. The stages include, analyze, design, development, implementation and evaluation. Product trials were conducted for students of class X MIPA program in SMA Negeri 1 Pejagoan. To get the interpretation of the data obtained, data analysis is performed by changing the score from a scale of four into a percentage. Then calculate the value of the Percentage Agreement (PA) to determine the reliability of the implementation of learning. As well as normalized gain to determine the increase in HOTS of students from the results of pre-test and post-test. The results of the validation test, the average of the three validators was 3.48. So that this CORE-based Physics handout is in the